APLIKASI PEMBELAJARAN KITAB AKHLAK LIL BANINDI PONDOK PESANTREN AL MUHTAROMLOWAYU DUKUN GRESIK - Salman Zahidi; M. Badruddin (Akademika, 2017)
The book that studied here is the Book of Akhlak lil banin.The Book of Akhlak lil banin is one of the most basic moral books are good for teaching morals new students or students who study at Moslem boarding school, because of this book describes some character that deserves to be emulated and avoided by students.This research was conducted to find out about how the book of Akhlak lil banin learning applications in Moslem boarding school of Al Muhtarom Lowayu Dukun Gresik and factors supporting and inhibiting about learning application of Akhlak lil banin book and how to overcome them.This study uses qualitative descriptive method. In this case the data collection techniques used through observation, interviews and documentation.Based on the research obtained by researcher from the field can be concluded that the application of learning the book of Akhlak lil banin in Moslem boarding school of  Al Muhtarom Lowayu Dukun Gresik is very good for making students disciplined in all circumstances.Keywords: The book that studied, Akhlak Lil Banin